Wild cards, weak signals and organisational improvisation - Mendonça, S.; Cunha, M. P. E.; Kaivo-oja, J.; Ruff, F. (Futures, 2004)
This paper addresses the need for reliable action guidelines which can be used by organisations in turbulent environments. Building on current conceptual and empirical research, we suggest an analytical approach to the management of surprising and potentially damaging events. In order to do so we propose the wild card management system. Wild cards refer to sudden and unique incidents that can constitute turning points in the evolution of a certain trend. As the first of the two components of such a wild card system, we advocate a weak signal methodology to take into account those wild cards that can be anticipated by scanning the decision environment. The second component, the nurture of improvisation capabilities, is designed to deal with unanticipated ongoing crises. This paper can be seen as part of a broader agenda on how to manage in conditions of continuous but unpredictable change.